2022
DOI: 10.51470/plantarchives.2022.v22.no1.041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Pesticide Treatment Dose on the Biochemical Response of the Potato Plants (Solanum Tuberosum L.)

Abstract: In order to enhance and protect crop yields from different pests, the use of pesticides has increased. In Algeria, most often farmers do not respect the recommended dose of pesticides. The aim of this study is to investigate the dose effect of applying pesticides in field conditions at standard and double doses (agronomic dose, AD; agronomic double dose, ADD) on the morphological and biochemical responses of potato plants (Solanum tuberosum L.). Our result showed significant effect of pesticide application on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Pesticide concentration increases have been observed to be moderately associated with the oxidative stress generated by pesticide application 31 . In the current study, the antioxidant enzyme activities and genes of potato plants increased at different concentrations of thiamethoxam as compared with the control, and the results are consistent with research by Amiri et al 32 . who discovered that the biochemical and antioxidant characteristics of the potato plant were significantly affected by the application of pesticides.…”
Section: Discussionsupporting
confidence: 91%
“…Pesticide concentration increases have been observed to be moderately associated with the oxidative stress generated by pesticide application 31 . In the current study, the antioxidant enzyme activities and genes of potato plants increased at different concentrations of thiamethoxam as compared with the control, and the results are consistent with research by Amiri et al 32 . who discovered that the biochemical and antioxidant characteristics of the potato plant were significantly affected by the application of pesticides.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results obtained by Amiri et al. (2022) shows significant effect of pesticide application on the biochemical and antioxidant properties of potato plants. The authors noticed an increase in the phenolic, flavonoid, and proline contents and a decrease in the chlorophyll and carotenoids.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that treatments based on butachlor (H), chlorpyrifos (I), and tricyclazole (F) modulate the carbohydrate, amino acid, and fatty acid metabolism [6], while the herbicides linuron, clomazone, and metribuzin cause an increase in polyphenol content [7]. Amiri et al [8] determined a decrease in photosynthetic dyes and improvements in phenolic compounds, flavonoids, and carbohydrate levels in potato under exposure to different types of pesticides: abamectin (I), cymoxanil (F), and metribuzin (H). As agents supporting the health of the target plant, biostimulators can mitigate the adverse effects of oxidative stress [9].…”
Section: Introductionmentioning
confidence: 99%